The Urgency of Cybercrime Law Reform in Indonesia: Resolving Artificial Intelligence Criminal Liability - Kurnia Dewi Anggraeny; Mufti Khakim; Muhammad Rizal Sirojudin (JUSTISI, 2025)
The existence of AI is a separate system based on logic, where the information entered into the system will be processed with a programmed algorithm to determine a predetermined result. AI can cause various forms of harm to everyone, including its creator, and the harm it causes can have a long-lasting impact, considering that AI can make decisions similar to humans. The application of AI in the industrial sector will impact all existing systems, including the criminal justice system in all countries. Therefore, the legal regulation of cybercrime in Indonesia needs to be reformed to resolve criminal liability for criminal acts that AI can carry out. The formulation of the problem in this study is what is the urgency of updating cybercrime law in Indonesia. Furthermore, how is the legal policy on criminal liability for artificial intelligence resolved it. Thus,  this study normative such as legal research carried out by examining library materials or data using statutory and analytical approaches. This study concludes and suggests that responsibility must be imposed on AI users and legal entities whose responsible parties are company directors. AI creators must also be responsible for the AI's actions. The renewal of cyber law in Indonesia is significant and should be done immediately, even in the Electronic Information and Transactions Law. Almost all institutional and personal documents are stored electronically; the state must also protect them. Other parties can then misuse these documents, which can be traded on the cyber black market and used irresponsibly. Illegal activities in cyberspace are also increasing, and the diversity of their actions with various skills is constantly increasing.